Association of IL-1β and IL-1 receptor antagonist haplotypes with rate of decline in lung function in smokers. Issue 11 (1st November 2001) - Joos, L; McIntyre, L; Ruan, J; Connett, J E; Anthonisen, N R; Weir, T D; Paré, P D; Sandford, A J
Abstract : BACKGROUND: There is increasing evidence that the cytokine network is central to the immunopathology of inflammatory airway diseases. The interleukin 1 (IL-1) receptor antagonist (IL-1RN) is a naturally occurring anti-inflammatory agent that binds to the IL-1 receptor but does not possess agonist activity. Each of the genes of the IL-1 locus on chromosome 2q14 is polymorphic. The IL1RN gene contains an 86 bp tandem repeat and allele 2 of this polymorphism has been associated with various inflammatory diseases. The IL-1β ( IL1B ) gene contains a promoter polymorphism (C-511T) that has been associated with inflammatory diseases and is in linkage disequilibrium with the IL1RN polymorphism. METHODS: We investigated whether polymorphisms in the IL1B and IL1RN genes were associated with rate of decline of lung function. Genotypes were determined in 284 smokers with a rapid decline in lung function and 306 smokers with no decline in lung function. RESULTS: None of the genotypes was associated with the rate of decline of lung function. However, the distribution of IL1B/IL1RN haplotypes was different between smokers with a rapid decline in lung function and those with no decline in lung function (p=0.0005). CONCLUSION: These results suggest that IL1B/IL1RN haplotypes play a role in the rate of decline in lung function in smokers.